2023
DOI: 10.3892/ijo.2023.5514
|View full text |Cite
|
Sign up to set email alerts
|

Tumor suppressive functions of hsa‑miR‑34a on cell cycle, migration and protective autophagy in bladder cancer

Abstract: Bladder cancer (BC) cells exhibit a high basal level of autophagy activity, which contributes to the development of a protective mechanism for cellular survival against current treatments. Hsa-microRNA-34a (miR-34a) presents anti-tumor function in several types of cancer. However, the functional mechanism of miR-34a in regulating tumor aggressiveness and protective autophagy of BC remains largely unknown. First, transfected BC cells with miR-34a mimic exhibited LC3-II and p62 accumulation through immunofluores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Its unique mechanism involves inhibiting the shedding of exosomes and inducing cellular senescence through the regulation of RAB27B expression. This finding opens up new avenues for targeting AML stem cells to improve treatment outcomes [127].…”
Section: The Role Of Mir-34s In Leukemiamentioning
confidence: 98%
“…Its unique mechanism involves inhibiting the shedding of exosomes and inducing cellular senescence through the regulation of RAB27B expression. This finding opens up new avenues for targeting AML stem cells to improve treatment outcomes [127].…”
Section: The Role Of Mir-34s In Leukemiamentioning
confidence: 98%
“…A study conducted by Cheng et al (Cheng et al 2004) indicated that the main susceptible population of SCNEC were older adults with smoking history, bladder stones, urinary tract infections, and other susceptibility factors. In addition, SCNEC was also reported to be related to the loss of tumor suppressor genes (e.g., p16), the ampli cation of oncogenic genes (e.g., c-Myc) and the methylation of tumor suppressor factors (Hwang et al 2023; Ke et al 2022).…”
Section: Introductionmentioning
confidence: 99%